Biodecolorization and degradation of textile azo dyes using Lysinibacillus sphaericus MTCC 9523 - Srinivasan, Shantkriti; Bankole, Paul Olusegun; Sadasivam, Senthil Kumar (Frontiers in Environmental Science, 2022)
Wastewater discharges by textile industries constitute a major environmental concern as they exert grave human health dangers. Innovative, cost-effective and economical strategy aimed at ameliorating the effect of textile effluent in the environment is highly desirable. Hence, this study investigated the decolorization efficiency of selective reactive azo dyes by textile effluent non-adapted Lysinibacillus sphaericus MTCC 9523 in optimized operational conditions. Visual color changes with 96.30 % and 92.71 % decolorization for Reactive Yellow F3R (RYF3R) and Joyfix Red RB (JRRB) elucidated by UV-visible spectrophotometric analysis affirmed decolorization of the dyes. Meanwhile, Fourier Transform Infrared (FTIR) Spectroscopy of the metabolites obtained after degradation further revealed the functional groups and loss of peak for azo group indicated the breaking of azo bond. On High-Performance Liquid Chromatography (HPLC) analysis, difference in control dye's retention time compared to treated sample with peaks at 2.413 and 2.895 min for RYF3R and 2.466 min and 1.640 min for Joyfix Red RB supported biodegradation by this organism. The chemical identities of the metabolites revealed after Gas Chromatography-Mass Spectrometry (GC-MS) analysis was used in the prediction of each dye’s metabolic pathway of degradation based on their molecular weight and mass-to-charge ratio. They were found to be (2Z)-but-2-ene, 1,3,5-triazine, (3E)-penta-1,3-diene for RYF3R and (methylsulfonyl)benzene, phenol, buta-1,3-diene, 1,3,5-triazine-2,4(1H,3H)-dione, nitrobenzene for JRRB. Overall, the use of adapted and non-adapted microbes is highly promising as an efficient, cost-effective, time-saving and universal green strategy for biodegradation of textile effluent containing azo dyes.